2022
DOI: 10.1029/2021gl097640
|View full text |Cite
|
Sign up to set email alerts
|

Nonagricultural Emissions Dominate Urban Atmospheric Amines as Revealed by Mobile Measurements

Abstract: As the derivatives of ammonia (NH 3 ), gaseous amines are a class of organic vapors containing a basic nitrogen atom with a lone pair, where one or more hydrogen atoms are substituted by organic functional groups, for example, an alkyl or aryl group (Qiu & Zhang, 2013). Since ambient concentration of amines (typically in the range of ppt) is 1-3 orders of magnitude lower than that of ammonia (NH 3 ;Kuhn et al., 2011), this poses a significant analytical challenge for environmental monitoring (Szulejko & Kim, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Recent studies based on nitrogen isotopic ratio (δ 15 N) measurements of gaseous NH 3 and particulate ammonium (NH 4 + ) salt indicate that ambient NH 3 is dominated by non-agriculture sources in urban Beijing . Similar results have also been found in Xi’an and the Yangtze River Delta region of China …”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Recent studies based on nitrogen isotopic ratio (δ 15 N) measurements of gaseous NH 3 and particulate ammonium (NH 4 + ) salt indicate that ambient NH 3 is dominated by non-agriculture sources in urban Beijing . Similar results have also been found in Xi’an and the Yangtze River Delta region of China …”
Section: Introductionmentioning
confidence: 53%
“…It is well-accepted that agriculture-related emissions dominate the global NH 3 budget in the atmosphere. However, several recent field studies demonstrated that nonagricultural emissions are the primary NH 3 sources in many urban areas in China. Therefore, atmospheric models based on emission inventories concentrated on agricultural emissions may not realistically simulate the atmospheric environment, particularly in the populated megacities of China. , Recently, NH 3 , amines, amides, and imines emission characteristics of motor vehicles have been determined explicitly through in situ roadside measurements . However, the emission features from many other anthropogenic activities are still unknown.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy among various studies might be a result of different levels of organic nitrogenous matters in different oceanic regions. In other words, the coastal seawater can be significantly influenced by anthropogenic activities such as agriculture, industrial wastewater discharge, and human excretion, which have been demonstrated as important sources of atmospheric amines (Chang et al, 2021(Chang et al, , 2022Ge et al, 2011a;Liu et al, 2022). These emission sources may also affect the rivers along the cities and the coastal oceans through the wastewater discharge and underground water.…”
Section: Contribution Of Sea Surface Organic Nitrogenous Reservoir To...mentioning
confidence: 99%
“…Chang et al. (2022) suggested that the textile production process was a primary source of C2‐amines in Suzhou, China. The global emissions of MA from animal husbandry were estimated to be ∼24 Gg N yr −1 (Schade & Crutzen, 1995).…”
Section: Introductionmentioning
confidence: 99%